Impact of Antiretroviral Therapy Duration on Hematology Profile in HIV Patients at Buntok Health Center, Indonesia - Wulandari, Eka Dwi; Norsiah, Wahdah; Insana, Aima (Baiman Bauntung Batuah Center, 2025)
HIV/AIDS is a global health challenge that requires long-term therapy, one of which is the use of Antiretroviral (ARV). ARV therapy has a significant impact on the patient's hematological profile, such as hemoglobin, hematocrit, erythrocytes, leukocytes, and platelets. However, the long-term effects of ARV therapy on hematological profiles in Indonesia, especially in the Central Kalimantan region, have not been widely studied. This study aims to analyze the relationship between the length of ARV therapy and hematological profile in HIV patients at Buntok health center. This study used an analytic survey design with a cross-sectional approach. The study sample involved 29 HIV patients undergoing ARV therapy, taken by total sampling. Data were obtained from medical records and laboratory examinations and then analyzed using the Spearman correlation test to test the relationship between variables. The results showed a significant association between the duration of ARV therapy and the levels of hemoglobin (p = 0.005), hematocrit (p = 0.001), erythrocytes (p = 0.000), and platelets (p = 0.023). However, no significant relationship was found between the duration of ARV therapy and the number of leukocytes (p = 0.063). The correlation found was negative, indicating that the longer the ARV therapy, the more certain hematological parameters decreased. It is concluded that the duration of ARV therapy is associated with changes in the hematological profile of HIV patients. These findings suggest the importance of routine monitoring of hematologic profiles to detect adverse effects of ARV therapy, especially in patients on long-term therapy.